Application of Population Pharmacokinetic Modeling for Individualized Infliximab Dosing Strategies in Crohn Disease. Issue 6 (December 2017) - Frymoyer, Adam; Hoekman, Daniël R.; Piester, Travis L.; de Meij, Tim G.; Hummel, Thalia Z.; Benninga, Marc A.; Kindermann, Angelika; Park, K.T.
ABSTRACT: Objectives: The pharmacokinetics of infliximab (IFX) is highly variable in children with Crohn disease (CD), and a one-size-fits-all approach to dosing is inadequate. Model-based drug dosing can help individualize dosing strategies. We evaluated the predictive performance and clinical utility of a published population pharmacokinetic model of IFX in children with CD. Methods: Within a cohort of 34 children with CD who had IFX trough concentrations measured, the pharmacokinetics of each patient was estimated in NONMEM using a published population pharmacokinetic model. Infliximab concentrations were then predicted based on each patient's dosing history and compared with actual measured concentrations (n = 59). In addition, doses 5 to 10 mg/kg and dosing intervals every 4 to 8 weeks were simulated in each patient to examine dose-trough relationships. Results: Predicted concentrations were within ±1.0 μg/mL of actual measured concentrations for 88% of measurements. The median prediction error (ie, measure of bias) was −0.15 μg/mL (95% confidence interval −0.37 to −0.05 μg/mL) and absolute prediction error (ie, measure of precision) was 0.26 μg/mL (95% confidence interval 0.15 to 0.40 μg/mL). At standard maintenance dosing of 5 mg/kg every 8 weeks, a trough >3 μg/mL was predicted to be achieved in 32% of patients. To achieve a trough >3 μg/mL, a dosing interval ⩽every 6 weeks was predicted to be required in 29% of patients. Conclusions: A published IFX population pharmacokinetic model demonstrated accurate predictive performance in a pediatric CD population. Individualized IFX dosing strategies in children with CD will be critical to consistently achieve trough concentrations associated with optimal outcomes.